Using eye-tracking to examine the role of first and second language glosses. (November 2022) - Kang, Hyeonah; Kweon, Soo-Ok; Choi, Sungmook
This study employs eye-tracking to investigate how first (L1) and second language (L2) glosses affect lexical uptake and reading behaviors in L2 learners of English. The study also explores the relationship between lexical uptake and reading behaviors as a function of gloss type. To investigate this, 81 Korean university students were asked to read a baseline passage with no gloss or the same passage with glosses in the study's L1 (Korean) or L2 (English). Their eye movements were recorded with an eye tracker as they read, and they were subsequently asked to respond to two vocabulary tests. Analyses of eye-tracking data and vocabulary test scores revealed that the presence or absence of L1 and L2 glosses might produce differences in lexical uptake and dissimilar attentional mechanisms. For instance, the study found that L1 and L2 glosses failed to significantly enhance the acquisition of visual word forms, whereas both types of glosses were significantly effective in consolidating form–meaning associations. Additionally, correlation analyses indicated that the relationship between reading behaviors and lexical acquisition might differ depending on gloss type. Ultimately, our findings provide a more comprehensive picture of L1 and L2 gloss effects, and have significant implications for L2 pedagogy.